2021
DOI: 10.1186/s12879-021-06626-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical implications of asymptomatic malaria and schistosomiasis co-infections in a rural community in western Kenya

Abstract: Background Malaria and schistosomiasis present considerable disease burden in tropical and sub-tropical areas and severity is worsened by co-infections in areas where both diseases are endemic. Although pathogenesis of these infections separately is well studied, there is limited information on the pathogenic disease mechanisms and clinical disease outcomes in co-infections. In this study, we investigated the prevalence of malaria and schistosomiasis co-infections, and the hematologic and blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
(44 reference statements)
2
7
1
Order By: Relevance
“…This finding was similar to studies conducted in Ethiopia that found significantly higher values of ALT, AST, direct bilirubin, and lower values of glucose and total protein in the S. mansoni monoinfected participants as compared to healthy participants [ 39 , 40 ]. In addition, this finding was similar with a study conducted in Western Kenya that found significantly higher median value of ALT in the malaria and S. mansoni -coinfected participants as compared to healthy participants [ 23 ]. This finding was also consistent with a study conducted in Yemen, which found significantly higher levels of AST, ALT, total bilirubin, and direct bilirubin in malaria patients compared to healthy individuals [ 9 ].…”
Section: Discussionsupporting
confidence: 89%
“…This finding was similar to studies conducted in Ethiopia that found significantly higher values of ALT, AST, direct bilirubin, and lower values of glucose and total protein in the S. mansoni monoinfected participants as compared to healthy participants [ 39 , 40 ]. In addition, this finding was similar with a study conducted in Western Kenya that found significantly higher median value of ALT in the malaria and S. mansoni -coinfected participants as compared to healthy participants [ 23 ]. This finding was also consistent with a study conducted in Yemen, which found significantly higher levels of AST, ALT, total bilirubin, and direct bilirubin in malaria patients compared to healthy individuals [ 9 ].…”
Section: Discussionsupporting
confidence: 89%
“…Parasitic coinfections have been reported in several studies, as recently reviewed [8], among which are P. falciparum and S. mansoni coinfection [6][7][8]. In this study, we present ndings of a cross-sectional analysis set out to ascertain the association between S. mansoni infection and P. falciparum infection.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, WHO estimated 249 million malaria cases in the endemic areas [3]. Malaria and schistosomiasis coinfection has been reported in areas with high occurrence of both infections [6][7][8]. Additionally stunting among children has been shown in S. mansoni as well as P. falciparum [9] infection Coinfection of malaria and schistosomiasis is particularly common in sub Saharan Africa (SSA) [10].…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 It causes schistosomiasis and has been rated as the second most harmful parasite in the world; only malaria has been stated to cause more mortality. 3 , 4 Schistosoma mansoni is endemic in Africa, South America, the Caribbean, and the Middle East. 5 Schistosomiasis is an intestinal infection that produces acute symptoms of diarrhoea, 6 abdominal pain, 6 and fever.…”
Section: Introductionmentioning
confidence: 99%